Nano-Structured Dilute Magnetic Semiconductors for Efficient Spintronics at Room Temperature - Gupta, Akanksha; Zhang, Rui; Kumar, Pramod; Kumar, Vinod; Kumar, Anup (Magnetochemistry, 2020)
In recent years, many efforts have been made to develop advanced metal oxide semiconductor nanomaterials with exotic magnetic properties for modern applications w.r.t traditional analogues. Dilute magnetic semiconductor oxides (DMSOs) are promising candidates for superior control over the charge and spin degrees of freedom. DMSOs are transparent, wide band gap materials with induced ferromagnetism in doping, with a minor percentage of magnetic 3d cation to create a long-range antiferromagnetic order. Although significant efforts have been carried out to achieve DMSO with ferromagnetic properties above room temperature, it is a great challenge that still exists. However, TiO2, SnO2, ZnO and In2O3 with wide band gaps of 3.2, 3.6, 3.2 and 2.92 eV, respectively, can host a broad range of dopants to generate various compositions. Interestingly, a reduction in the size of these binary oxides can induce ferromagnetism, even at room temperature, due to the grain boundary, presence of defects and oxygen vacancies. The present review provides a panorama of the structural analysis and magnetic properties of DMSOs based on binary metal oxides nanomaterials with various ferromagnetic or paramagnetic dopants, e.g., Co, V, Fe and Ni, which exhibit enhanced ferromagnetic behaviors at room temperature.